2010
DOI: 10.1007/s00392-010-0226-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oxygen uptake efficiency slope as a marker of cardiorespiratory reserve on response to cardiac resynchronization therapy

Abstract: Nonresponders to CRT showed a more preserved cardiorespiratory functional reserve as compared to responders despite similar NYHA classification. Evaluation of the OUES by submaximal exercise testing improves identification of responders to CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…To our knowledge, this is one of the first studies that show that submaximal exercise parameters can help in predicting outcome of CRT. Previously, Berger et al showed that the OUES at baseline was related to the CRT response 21. However, we were unable to reproduce the high sensitivity and specificity of OUES that was reported.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…To our knowledge, this is one of the first studies that show that submaximal exercise parameters can help in predicting outcome of CRT. Previously, Berger et al showed that the OUES at baseline was related to the CRT response 21. However, we were unable to reproduce the high sensitivity and specificity of OUES that was reported.…”
Section: Discussionmentioning
confidence: 55%
“…Previously, Berger et al showed that the OUES at baseline was related to the CRT response. 21 However, we were unable to reproduce the high sensitivity and specificity of OUES that was reported. VO 2 peak and VE/VCO 2 slope were shown to be related to CRT response in other studies, possibly because of their higher sample size.…”
Section: Discussionmentioning
confidence: 84%
“…No entanto, a literatura tem mostrado que a mensuração do VO 2 pico pode ter um viés por ser altamente influenciado pela motivação do paciente e do investigador24,25 . Devido a essas limitações na mensuração do VO 2 pico, vários investigadores têm utilizado parâmetros de exercício submáximo para reproduzir o desempenho geral do indivíduo26,27,28 .O parâmetro submáximo capaz de avaliar de forma global a eficiência cardiorrespiratória frente à realização do exercício físico é o chamado slope da eficiência do consumo de oxigênio ou oxygen uptake efficiency slope (OUES)29 .Fisiologicamente, o OUES é definido como a taxa de aumento no consumo de oxigênio em resposta ao aumento na ventilação pulmonar29 , sendo um índice que indica a eficiência na captação de oxigênio pelos pulmões e sua extração em nível periférico30 .Mais especificamente, o OUES reflete a combinação das modulações cardiovasculares, musculoesqueléticas e pulmonares, podendo ser afetado tanto pelo metabolismo muscular como alterações na relação ventilação-perfusão em nível pulmonar29,77 . Por exemplo, estudos prévios demonstraram que pacientes com insuficiência cardíaca apresentam acidose metabólica precoce durante a realização do exercício físico em comparação a indivíduos saudáveis, dessa forma levando a uma diminuição do OUES78,79 .…”
unclassified